Mobile GIS occupancy audit of Ulana informal settlement in Ekurhuleni municipality, South Africa. Issue 4 (2nd October 2018) - Mokoena, Baleseng Tlholohelo; Musakwa, Walter
ABSTRACT: Relocating people in informal settlements and upgrading the lives of those people require consistent commitment, good strategies, and supporting systems. In South Africa, in order to allocate subsidized housing to beneficiaries of an informal settlement, beneficiary administration needs to determine the number of people who qualify for subsidized houses. Without geo-spatial data-based technical verification, conventional methods of occupancy audits are often cumbersome, are unreliable, and do not promote smart and evidence-based decision making. Accordingly, the aim of this study is to propose and develop an Oracle-based mobile GIS tool to conduct an occupancy audit for Ulana, an informal settlement in Ekurhuleni Municipality in South Africa. Android-based tablets were used to collect the geographic and socio-economic attributes of the informal dwelling units (DU). Spatial analysis (in ArcGIS software and geo-spatial modeling environment) and statistical analysis were conducted to produce the occupancy audit. The results indicated that the use of mobile GIS provides up-to-date, accurate, comprehensive, and real-time data so as to facilitate the development of smart and integrated human settlements. The results of this audit also indicated that only 57% of the households residing in Ulana could potentially benefit from receiving a subsidized house. Accordingly, the occupancy audit enables planners to plan appropriate upgrading and housing development strategies for informal settlement. This study demonstrates that successful planning of housing delivery for post independent integrated neighborhoods is not a mere political rhetoric but is viable when it is based on reasonable geo-spatial techniques and information. The use of mobile GIS therefore needs to be extended to other informal settlement upgrading projects in South Africa as well as other cities in the global south. However, proper professional training is required to ensure the successful usage of smart mobile GIS tools.